Large-size ultrathin aluminum oxide reinforced copper-based foil and preparation method thereof
By magnetron sputtering copper plating on an aluminum substrate, combined with stacking, annealing and high-temperature oxidation, the problem of difficulty in preparing large strips of diffusion reinforced copper materials in the prior art was solved, and ultra-thin alumina reinforced copper base foil with excellent performance was successfully prepared.
Patent Information
- Application Number
- CN202411580461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
AI Technical Summary
It is difficult to prepare large plate and strips for existing diffuse reinforced copper materials, and poor processing plasticity is prone to cracking, which limits its application as a high-end lead frame material.
Copper is plating with magnetron sputtering on an aluminum substrate, and superimposed rolling and intermediate annealing, followed by graded annealing to form a copper-aluminum alloy, and then coated with metal oxide powder for high-temperature oxidation, and finally pickling and hydrogen reduction in an argon atmosphere to prepare an ultra-thin alumina-strengthening copper-based foil.
The preparation of large-size ultra-thin alumina reinforced copper-based foil is realized. The thickness of the material can reach below 12 microns, the hardness is above 100Hv, the conductivity is above 90%, and the softening temperature is above 750℃.
Smart Images

Figure CN119588751A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal composite materials, and particularly relates to a large-size ultra-thin alumina reinforced copper-based foil and a preparation method thereof. Background Art
[0002] Dispersion-strengthened copper (aluminum oxide reinforced copper-based composite material) is difficult to prepare large plates and strips, which limits the application of this type of material as a high-end lead frame material. The main reason is that the current method used for this type of material is to use cuprous oxide and copper-aluminum alloy powder as raw materials, and prepare bulk materials through powder metallurgy methods such as pressing and high-temperature sintering (internal oxidation), and then prepare plate and strip materials through rolling. However, there are pores inside the powder metallurgy products and the processing plasticity is poor, which makes this type of material easy to crack during processing.
[0003] Therefore, a new preparation process of alumina reinforced copper-based foil is needed to prepare large pieces of plate and strip with good performance. Summary of the invention
[0004] The object of the present invention is to provide a large-sized ultra-thin alumina reinforced copper-based foil and a preparation method thereof, so as to solve the technical problems in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a large-size ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) magnetron sputtering copper is plated on an aluminum substrate to form a copper coating on the surface of the cleaned aluminum substrate, and then laminated with a copper strip to obtain a copper-plated laminated strip; In the above process, copper is sputtered on aluminum, and then it is laminated with pure copper. Pure copper is used to control the ratio of copper and aluminum oxide in the final dispersed copper. The mass content of aluminum is 0.2%.
[0006] Step (2) subjecting the copper-plated laminated strip to laminated rolling and intermediate annealing to obtain a laminated rolled strip; Through the above technical scheme, intermediate annealing can increase the processing rate of the rolled strip. Only when the number of rolled strips is large can the aluminum layer be fully refined, so that it can be fully dissolved in copper to become solid solution atoms in the subsequent heat treatment process (the deformation energy storage caused by the accumulated deformation of the rolled strip is also one of the reasons that promote the dissolution of aluminum in copper); the initial heat treatment temperature is low in order to avoid the formation of Cu-Al intermediate phase as much as possible, and even if it is formed, it is a smaller intermediate phase; in addition to obtaining the solid solution effect of aluminum in copper, rolled strips and heat treatments have another important goal, which is to completely dissolve aluminum in copper to form a complete solid solution to increase the melting point of the material. If a complete solid solution cannot be achieved, even if there is only a small amount of elemental aluminum, the subsequent high-temperature internal oxidation process will cause the aluminum to melt, thereby causing the material preparation to fail.
[0007] Step (3) subjecting the laminated strip to graded annealing to obtain a copper-aluminum alloy strip; Through the above technical scheme, aluminum is fully diffused in copper to form a copper-aluminum alloy with a melting point exceeding 1000°C. After rolling, the thickness of the aluminum layer and the copper layer are controlled, and then the aluminum is dissolved into the copper to become solute atoms through heat treatment. Finally, a relatively uniform copper-aluminum solid solution is formed through heat treatment. By controlling multiple graded annealing and insulation sections, it is ensured that all the aluminum can be dissolved into the copper below the melting point of aluminum to form solid solution atoms. The copper-aluminum solid solution also has high and low melting points. Setting multiple insulations above the melting point of aluminum can avoid the melting of the copper-aluminum solid solution, thereby forming a copper-aluminum solid solution with a high solute content.
[0008] Step (4) coating the surface of the copper-aluminum alloy strip with metal oxide powder, rolling it, and then oxidizing it at high temperature in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) The alumina dispersion strengthened copper foil is passed through a pickling tank filled with nitric acid solution, and then rinsed through a clean water tank, and then hydrogen is introduced to react to obtain an ultra-thin alumina strengthened copper-based foil.
[0009] In the above process, the copper oxide residue on the surface is removed and reduced with hydrogen to further improve the conductivity.
[0010] Preferably, in step (1), the method of magnetron sputtering copper plating is as follows: placing an aluminum substrate in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 150-300V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions, which are accelerated by an electric field and bombarded on the cathode copper target, and copper atoms are sputtered out and deposited on the surface of the anode aluminum substrate to form a copper coating.
[0011] Preferably, in step (1), the aluminum substrate is 12 micrometer aluminum foil, and the copper coating thickness is 20-30 nm.
[0012] Preferably, in step (2), the annealing and intermediate annealing methods are as follows: the annealing temperature after the first lap rolling is 200°C and the time is 36 hours; the annealing temperature after the second lap rolling is 220°C and the time is 30 hours; the annealing temperature after the third lap rolling is 240°C and the time is 24 hours; the annealing temperature after the fourth lap rolling is 280°C and the time is 18 hours; the annealing temperature after the fifth lap rolling is 320°C and the time is 12 hours; the annealing temperature after the sixth lap rolling is 360°C and the time is 8 hours; the annealing temperature after the seventh lap rolling is 400°C and the time is 4 hours.
[0013] Preferably, in step (2), the thickness of the laminated strip is 10-14 um.
[0014] Preferably, in step (2), the rolling reduction rate is 30-40%.
[0015] Preferably, in step (3), the graded annealing step is: keeping warm at 400-430°C for 6h, keeping warm at 450-480°C for 6h, keeping warm at 500-560°C for 6h, keeping warm at 570-600°C for 4h, keeping warm at 620-650°C for 4h, keeping warm at 670-700°C for 4h, keeping warm at 710-730°C for 4h, keeping warm at 750-780°C for 4h, keeping warm at 790-810°C for 4h, keeping warm at 820-850°C for 4h, and keeping warm at 860-890°C for 4h.
[0016] Preferably, in step (4), the metal oxide is one of cupric oxide and cuprous oxide.
[0017] Preferably, in step (4), the coating thickness is 40-60 μm and the high temperature oxidation temperature is 800-900°C.
[0018] Preferably, in step (5), the speed of passing the alumina dispersion strengthened copper foil through the pickling tank filled with nitric acid solution is 1-2 m / s; the flow rate of hydrogen is 100-300 mL / min; the reaction conditions are: reaction temperature is 200-400°C, and reaction time is 0.5-1.5 h.
[0019] The large-size ultra-thin alumina reinforced copper-based foil is prepared by the method for preparing the large-size ultra-thin alumina reinforced copper-based foil.
[0020] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: The ultra-thin alumina reinforced copper-based foil obtained by magnetron sputtering copper plating on an aluminum substrate, performing multiple stacking and intermediate annealing, and further graded annealing, coating metal oxide powder, rolling and high-temperature oxidation can reach a larger size; the thickness of the ultra-thin alumina reinforced copper-based foil can reach less than 12 microns; the hardness is above 100Hv, the conductivity is above 90%, and the softening temperature is above 750°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is a process flow chart for preparing the large-sized ultra-thin alumina reinforced copper-based foil of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 See also Figure 1 As shown, this embodiment discloses a method for preparing a large-sized ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) placing a 12-micron aluminum foil in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 200 V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions and bombarding the cathode copper target with electric field acceleration, and depositing copper atoms on the surface of the anode aluminum substrate after being sputtered to form a copper coating, so that a 25 nm copper coating is formed on the surface of the cleaned aluminum substrate, and then laminating and rolling with a copper strip to obtain a copper-plated laminating strip with an aluminum mass content of 0.2%; Step (2) performing lamination and intermediate annealing on the copper-plated laminated strip, wherein the annealing temperature after the first lamination is 200°C and the time is 36 hours, the annealing temperature after the second lamination is 220°C and the time is 30 hours, the annealing temperature after the third lamination is 240°C and the time is 24 hours, the annealing temperature after the fourth lamination is 280°C and the time is 18 hours, the annealing temperature after the fifth lamination is 320°C and the time is 12 hours, the annealing temperature after the sixth lamination is 360°C and the time is 8 hours, and the annealing temperature after the seventh lamination is 400°C and the time is 4 hours, to obtain a laminated strip with a rolling reduction rate of 35%; Step (3) performing graded annealing on the laminated strip by keeping it at 420°C for 6 hours, keeping it at 470°C for 6 hours, keeping it at 530°C for 6 hours, keeping it at 590°C for 4 hours, keeping it at 640°C for 4 hours, keeping it at 690°C for 4 hours, keeping it at 720°C for 4 hours, keeping it at 760°C for 4 hours, keeping it at 800°C for 4 hours, keeping it at 830°C for 4 hours, and keeping it at 870°C for 4 hours to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with 15 μm copper oxide powder, and after rolling, performing high-temperature oxidation at 850° C. in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) passing the alumina dispersion strengthened copper foil through a pickling tank filled with nitric acid solution at a speed of 1.5 m / s, and rinsing it through a clean water tank, and then introducing hydrogen at a flow rate of 200 mL / min, and reacting at 300° C. for 1 hour to obtain an ultra-thin alumina strengthened copper-based foil.
[0025] Example 2 See also Figure 1 As shown, this embodiment discloses a method for preparing a large-sized ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) placing a 12-micron aluminum foil in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 150V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions and bombarding the cathode copper target with electric field acceleration, and depositing copper atoms on the surface of the anode aluminum substrate after being sputtered to form a copper coating, so that a 30nm copper coating is formed on the surface of the cleaned aluminum substrate, and then laminating and rolling with a copper strip to obtain a copper-plated laminating strip with an aluminum mass content of 0.2%; Step (2) performing annealing and intermediate annealing on the copper-plated laminated strip, wherein the annealing temperature after the first annealing is 200°C and the time is 36 hours, the annealing temperature after the second annealing is 220°C and the time is 30 hours, the annealing temperature after the third annealing is 240°C and the time is 24 hours, the annealing temperature after the fourth annealing is 280°C and the time is 18 hours, the annealing temperature after the fifth annealing is 320°C and the time is 12 hours, the annealing temperature after the sixth annealing is 360°C and the time is 8 hours, and the annealing temperature after the seventh annealing is 400°C and the time is 4 hours, to obtain a laminated strip with a rolling reduction rate of 30%; Step (3) performing graded annealing on the laminated strip by keeping it at 400°C for 6 hours, keeping it at 480°C for 6 hours, keeping it at 500°C for 6 hours, keeping it at 600°C for 4 hours, keeping it at 620°C for 4 hours, keeping it at 700°C for 4 hours, keeping it at 710°C for 4 hours, keeping it at 780°C for 4 hours, keeping it at 790°C for 4 hours, keeping it at 850°C for 4 hours, and keeping it at 860°C for 4 hours to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with 10 μm cuprous oxide powder, and after rolling, performing high-temperature oxidation at 800° C. in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) passing the alumina dispersion strengthened copper foil through a pickling tank filled with nitric acid solution at a speed of 2 m / s, and rinsing it through a clean water tank, and then introducing hydrogen at a flow rate of 100 mL / min, and reacting at 400° C. for 0.5 h to obtain an ultra-thin alumina strengthened copper-based foil.
[0026] Example 3 See also Figure 1 As shown, this embodiment discloses a method for preparing a large-sized ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) placing a 12-micron aluminum foil in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 300V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions and bombarding the cathode copper target with electric field acceleration, and depositing copper atoms on the surface of the anode aluminum substrate after being sputtered to form a copper coating, so that a 20nm copper coating is formed on the surface of the cleaned aluminum substrate, and then laminating and rolling with a copper strip to obtain a copper-plated laminating strip with an aluminum mass content of 0.2%; Step (2) performing annealing and intermediate annealing on the copper-plated laminated strip, wherein the annealing temperature after the first annealing is 200°C and the time is 36 hours, the annealing temperature after the second annealing is 220°C and the time is 30 hours, the annealing temperature after the third annealing is 240°C and the time is 24 hours, the annealing temperature after the fourth annealing is 280°C and the time is 18 hours, the annealing temperature after the fifth annealing is 320°C and the time is 12 hours, the annealing temperature after the sixth annealing is 360°C and the time is 8 hours, and the annealing temperature after the seventh annealing is 400°C and the time is 4 hours, to obtain a laminated strip with a rolling reduction rate of 40%; Step (3) performing graded annealing on the laminated strip by keeping it at 430°C for 6 hours, keeping it at 450°C for 6 hours, keeping it at 560°C for 6 hours, keeping it at 570°C for 4 hours, keeping it at 650°C for 4 hours, keeping it at 670°C for 4 hours, keeping it at 730°C for 4 hours, keeping it at 750°C for 4 hours, keeping it at 810°C for 4 hours, keeping it at 820°C for 4 hours, and keeping it at 890°C for 4 hours to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with 20 μm copper oxide powder, and after rolling, performing high-temperature oxidation at 900° C. in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) passing the alumina dispersion strengthened copper foil through a pickling tank filled with nitric acid solution at a speed of 1 m / s, and rinsing it through a clean water tank, and then introducing hydrogen at a flow rate of 300 mL / min, and reacting at 200° C. for 1.5 h to obtain an ultra-thin alumina strengthened copper-based foil.
[0027] Example 4 See also Figure 1 As shown, this embodiment discloses a method for preparing a large-sized ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) placing a 12-micron aluminum foil in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 170V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions and bombarding the cathode copper target with electric field acceleration, and depositing copper atoms on the surface of the anode aluminum substrate after being sputtered to form a copper coating, so that a 28nm copper coating is formed on the surface of the cleaned aluminum substrate, and then laminating and rolling with a copper strip to obtain a copper-plated laminating strip with an aluminum mass content of 0.2%; Step (2) performing lamination and intermediate annealing on the copper-plated laminated strip, wherein the annealing temperature after the first lamination is 200°C and the time is 36 hours, the annealing temperature after the second lamination is 220°C and the time is 30 hours, the annealing temperature after the third lamination is 240°C and the time is 24 hours, the annealing temperature after the fourth lamination is 280°C and the time is 18 hours, the annealing temperature after the fifth lamination is 320°C and the time is 12 hours, the annealing temperature after the sixth lamination is 360°C and the time is 8 hours, and the annealing temperature after the seventh lamination is 400°C and the time is 4 hours, to obtain a laminated strip with a rolling reduction rate of 32%; Step (3) performing graded annealing on the laminated strip by keeping it at 410°C for 6 hours, keeping it at 460°C for 6 hours, keeping it at 510°C for 6 hours, keeping it at 580°C for 4 hours, keeping it at 630°C for 4 hours, keeping it at 680°C for 4 hours, keeping it at 720°C for 4 hours, keeping it at 760°C for 4 hours, keeping it at 800°C for 4 hours, keeping it at 830°C for 4 hours, and keeping it at 870°C for 4 hours to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with 13 μm cuprous oxide powder, and after rolling, performing high-temperature oxidation at 820° C. in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) passing the alumina dispersion strengthened copper foil through a pickling tank filled with nitric acid solution at a speed of 1.5 m / s, and then rinsed through a clean water tank, and then hydrogen gas was introduced at a flow rate of 200 mL / min, and reacted at 300° C. for 1.5 h to obtain an ultra-thin alumina strengthened copper-based foil.
[0028] Example 5 See also Figure 1 As shown, this embodiment discloses a method for preparing a large-sized ultra-thin alumina reinforced copper-based foil, comprising the following steps: Step (1) placing a 12-micron aluminum foil in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 280V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions and bombarding the cathode copper target with electric field acceleration, and depositing copper atoms on the surface of the anode aluminum substrate after being sputtered to form a copper coating, so that a 22nm copper coating is formed on the surface of the cleaned aluminum substrate, and then laminating and rolling with a copper strip to obtain a copper-plated laminating strip with an aluminum mass content of 0.2%; Step (2) performing lamination and intermediate annealing on the copper-plated laminated strip, wherein the annealing temperature after the first lamination is 200°C and the time is 36 hours, the annealing temperature after the second lamination is 220°C and the time is 30 hours, the annealing temperature after the third lamination is 240°C and the time is 24 hours, the annealing temperature after the fourth lamination is 280°C and the time is 18 hours, the annealing temperature after the fifth lamination is 320°C and the time is 12 hours, the annealing temperature after the sixth lamination is 360°C and the time is 8 hours, and the annealing temperature after the seventh lamination is 400°C and the time is 4 hours, to obtain a laminated strip with a rolling reduction rate of 38%; Step (3) performing graded annealing on the laminated strip by keeping it at 420°C for 6 hours, keeping it at 460°C for 6 hours, keeping it at 550°C for 6 hours, keeping it at 590°C for 4 hours, keeping it at 630°C for 4 hours, keeping it at 690°C for 4 hours, keeping it at 720°C for 4 hours, keeping it at 770°C for 4 hours, keeping it at 800°C for 4 hours, keeping it at 830°C for 4 hours, and keeping it at 880°C for 4 hours to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with 18 μm copper oxide powder, and after rolling, performing high-temperature oxidation at 870° C. in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) passing the alumina dispersion strengthened copper foil through a pickling tank filled with nitric acid solution at a speed of 2 m / s, and rinsing it through a clean water tank, and then introducing hydrogen at a flow rate of 100 mL / min, and reacting at 400° C. for 0.5 h to obtain an ultra-thin alumina strengthened copper-based foil.
[0029] Experimental example The properties of the alumina reinforced copper-based foils prepared in Examples 1-5 were tested, and the test results are shown in Table 1: Table 1 Group Thickness / micron Hardness / Hv Conductivity / % Anti-softening temperature / ℃ Example 1 7 132 94 790 Example 2 9 125 92 760 Example 3 8 131 93 770 Example 4 10 122 93 780 Example 5 8 129 92 770 It can be seen from Table 1 that the alumina reinforced copper-based foil prepared in Examples 1-5 has good hardness, conductivity and softening resistance, and can be prepared in large sizes; the thickness of the dispersion-strengthened copper strip can reach less than 10 microns; the hardness is above 120Hv, the conductivity is above 90%, and the softening resistance is above 750°C.
[0030] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0031] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a large-size ultra-thin alumina reinforced copper-based foil, characterized in that: The following steps are involved: Step (1) magnetron sputtering copper is plated on an aluminum substrate to form a copper coating on the surface of the cleaned aluminum substrate, and then laminated with a copper strip to obtain a copper-plated laminated strip; Step (2) subjecting the copper-plated laminated strip to laminated rolling and intermediate annealing to obtain a laminated rolled strip; Step (3) subjecting the laminated strip to graded annealing to obtain a copper-aluminum alloy strip; Step (4) coating the surface of the copper-aluminum alloy strip with metal oxide powder, rolling it, and then oxidizing it at high temperature in an argon atmosphere to obtain an aluminum oxide dispersion-strengthened copper foil; Step (5) The alumina dispersion strengthened copper foil is passed through a pickling tank filled with nitric acid solution, and then rinsed through a clean water tank, and then hydrogen is introduced to react to obtain an ultra-thin alumina strengthened copper-based foil.
2. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (1), the method of magnetron sputtering copper plating is as follows: placing an aluminum substrate in a vacuum magnetron sputtering coating machine, using 99.99% pure copper as a cathode target and an aluminum substrate as an anode, applying a 150-300V DC voltage between the cathode target and the anode under the protection of an argon atmosphere, generating a magnetron type abnormal glow discharge in the coating machine, ionizing the argon gas into argon ions, and bombarding the cathode copper target with electric field acceleration, and copper atoms are sputtered out and deposited on the surface of the anode aluminum substrate to form a copper coating.
3. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (1), the aluminum substrate is 12 micron aluminum foil, the copper coating thickness is 20-30 nm, and the aluminum mass content of the copper-plated laminated strip is 0.2%.
4. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (2), the annealing and intermediate annealing methods are as follows: the annealing temperature after the first lap rolling is 200°C and the time is 36 hours; the annealing temperature after the second lap rolling is 220°C and the time is 30 hours; the annealing temperature after the third lap rolling is 240°C and the time is 24 hours; the annealing temperature after the fourth lap rolling is 280°C and the time is 18 hours; the annealing temperature after the fifth lap rolling is 320°C and the time is 12 hours; the annealing temperature after the sixth lap rolling is 360°C and the time is 8 hours; and the annealing temperature after the seventh lap rolling is 400°C and the time is 4 hours.
5. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (2), the thickness of the laminated strip is 10-14 um.
6. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (2), the rolling reduction rate is 30-40%.
7. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (3), the graded annealing step is: keeping warm at 400-430°C for 6 hours, keeping warm at 450-480°C for 6 hours, keeping warm at 500-560°C for 6 hours, keeping warm at 570-600°C for 4 hours, keeping warm at 620-650°C for 4 hours, keeping warm at 670-700°C for 4 hours, keeping warm at 710-730°C for 4 hours, keeping warm at 750-780°C for 4 hours, keeping warm at 790-810°C for 4 hours, keeping warm at 820-850°C for 4 hours, and keeping warm at 860-890°C for 4 hours.
8. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (4), the metal oxide is one of cupric oxide and cuprous oxide.
9. The method for preparing a large-size ultra-thin alumina reinforced copper-based foil according to claim 1, characterized in that: In the step (4), the coating thickness is 10-20 μm; and the high temperature oxidation temperature is 800-900°C.
10. A large-sized ultra-thin alumina reinforced copper-based foil prepared by the method according to any one of claims 1 to 9.